2011
DOI: 10.1002/j.2055-2335.2011.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Use in Inpatient Palliative Care

Abstract: Aim To describe the prescribing patterns of dexamethasone in a cohort of palliative care inpatients. Method Data were collected from a consecutive sample of patients admitted to 2 palliative care units over an 8 week period. Data on dexamethasone use was also collected, i.e. indication for use, dosages, concurrent medications, adverse effects, blood glucose levels and reasons for changes in dose. Results 359 patients were admitted during the recruitment period and 185 (52%) were prescribed dexamethasone. 37 (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 15 publications
(39 reference statements)
3
8
0
Order By: Relevance
“…The most frequent prescribing indication was non-specific (40.4%), again this is in line with international experience if a broad definition of non-specific is used [4,14]. While this is a notable result, given that there is relatively little published evidence to support the use of corticosteroids for non-specific reasons [48], it has to be interpreted with some caution because of varying definitions of non-specific indications in the literature.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The most frequent prescribing indication was non-specific (40.4%), again this is in line with international experience if a broad definition of non-specific is used [4,14]. While this is a notable result, given that there is relatively little published evidence to support the use of corticosteroids for non-specific reasons [48], it has to be interpreted with some caution because of varying definitions of non-specific indications in the literature.…”
Section: Discussionsupporting
confidence: 78%
“…They are commonly prescribed for patients in palliative care for both specific and non-specific indications [4-9]. Corticosteroids are potent medicines with frequent adverse effects and while the intent is to achieve beneficial results for the patient, the consequences of long-term use may counteract this objective [10].…”
Section: Introductionmentioning
confidence: 99%
“…A strength of this mixed-methods approach was that interviewees were able to comment on the summary data from the previous study which showed how prescribing practice at their hospice compared to others in the sample. To the best of our knowledge, this is the first qualitative study of its kind, although there have been a number of quantitative studies which have documented corticosteroid prescribing practices [ 1 5 , 7 , 9 – 12 ]. The interviews with clinicians yielded rich insights into the place of these drugs in palliative care and the main influences on their prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids are a potent group of medicines which have been used in palliative care since the late 1950s to alleviate both specific and non-specific debilitating symptoms [ 1 5 ]. The proportion of palliative care patients prescribed corticosteroids has been reported as ranging from 32% to 80%, with a median of about 60% [ 1 4 , 6 13 ]. In a recent New Zealand study of corticosteroid prescribing in palliative care, we observed that 65% of patients received at least one course of corticosteroids and there was a marked consistency in prescribing frequency across the six sample hospices (range: 61-69%) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation